Endogenous oxytocin is associated with the experience of compassion and recalled upbringing in Borderline Personality Disorder. Issue 1 (7th September 2017) - Ebert, Andreas; Edel, Marc‐Andreas; Gilbert, Paul; Brüne, Martin
Abstract : Background/Objective: The role of the neuropeptide oxytocin (OT) in Borderline Personality Disorder (BPD) is poorly understood. It is particularly unknown how early experiences with caregivers moderate the action of OT in BPD. Here, we examined the association of plasma OT levels in BPD patients with the experience of compassion and recalled parental behavior during childhood. Methods: Fifty‐seven BPD patients and 43 healthy controls participated in the study. OT plasma levels were analyzed by radioimmunoassay. Subjects additionally completed questionnaires focusing on fears of compassion (FOC) and recalled upbringing ("Questionnaire of Recalled Parental Rearing Behavior/Fragebogen zum erinnerten elterlichen Erziehungsverhalten, " FEE). Results: BPD patients had significantly lower OT plasma levels than healthy controls and differed significantly on all FOC and FEE scales; BPD patients had higher FOC scores (indicating more aversion of being compassionate to themselves and others and receiving compassion from others). They also differed in recalled parenting. In the BPD group, scores of the FOC scale "fear of compassion from others" were significantly negatively correlated with OT levels. Moreover, recalled "emotional warmth" of their parents during childhood was positively correlated with OT plasma levels of BPD subjects. No such correlations were found in the control group. Conclusion: Our results corroborate findings from previous studies reporting lower OT levels in patients with BPD. Moreover, peripheral OT seems to be linked with the tolerance of compassionate feelings and early experiences with caregivers. This is consistent with other findings that OT is an important mediator of the experience of emotional warmth from others.